1965
DOI: 10.1017/s0022112065000046
|View full text |Cite
|
Sign up to set email alerts
|

The viscous incompressible flow inside a cone

Abstract: The steady, axisymmetric, converging motion of a viscous incompressible fluid inside an infinite right circular cone is considered. It is shown that the exact solution of the Navier-Stokes equation for the stream function Ψ is of the form Ψ(r,θ) = AF(rv/A,θ), where (r, θ) are spherical polar co-ordinates chosen so r = 0 is the apex and θ = 0 is the axis of the cone, 2πA is the volumetric flow rate, and v the kinematic viscosity of the fluid. Asymptotic expansions of the stream function are found for large and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1967
1967
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…This is solved numerically and shows the transition to a plug flow, as found in the study of Vatistas & Ghaly (1999). The same PDE is obtained by Ackerberg (1965) for flow in a single cone, but not solved numerically. Further asymptotic approximation gives the structure of the boundary layers bounding the plug flow in terms of the solution of a third order ODE (again obtained by Ackerberg (1965)), which we solve numerically.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is solved numerically and shows the transition to a plug flow, as found in the study of Vatistas & Ghaly (1999). The same PDE is obtained by Ackerberg (1965) for flow in a single cone, but not solved numerically. Further asymptotic approximation gives the structure of the boundary layers bounding the plug flow in terms of the solution of a third order ODE (again obtained by Ackerberg (1965)), which we solve numerically.…”
Section: Introductionmentioning
confidence: 71%
“…The resulting converging or diverging flows are taken to be steady, axisymmetric, with no swirl component. This problem was considered for the case of a single cone by Bond (1927) and Ackerberg (1965), who suggested that a vortex motion might occur near the apex; this prediction was later discussed critically by Brown & Stewartson (1965) and has not been observed experimentally. Nonetheless the approach by Ackerberg (1965) has close links with our study as we indicate below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinate system used on the underlying conical substrate is shown on the right-hand side of Figure 2. This is essentially working in a polar coordinate system where the polar angle is fixed at φ as used in other studies [1,14,43].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…From that time applications have been presented by various authors [13][14][15][16][17]. Goldstein [13] has given the first, heuristic, discussion of existence and uniqueness.…”
Section: Introductionmentioning
confidence: 99%